The association between uncarboxylated matrix Gla protein and lipoprotein-associated phospholipase A2 - Mayer, Otto; Mlíková Seidlerová, Jitka; Vaněk, Jiří; Kielbergerová, Lenka; Bruthans, Jan; Filipovský, Jan; Wohlfahrt, Peter; Cífková, Renata; Trefil, Ladislav; Knapen, Marjo H J; Drummen, Nadja E A; Vermeer, Cees (Maturitas, 2015)
BACKGROUND: Lipoprotein-associated phospholipase A2 (Lp-PLA2) is independently associated with cardiovascular risk, probably via inflammatory activity in sclerotic plaque. We speculated whether Lp-PLA2 has a role in the aetiology of vascular calcifications, estimated from circulating uncarboxylated matrix Gla protein (MGP) species and whether we could find a potential interaction of Lp-PLA2 and MGP in terms of mortality. MATERIALS AND METHODS: We examined 798 patients (mean age 65.1 years) with stable vascular disease and followed them in a prospective study. Both, desphospho-uncarboxylated and total MGP (dp-ucMGP or t-ucMGP) were quantified by pre-commercial ELISA assays, developed by VitaK (Maastricht, The Netherland) RESULTS: Lp-PLA2 activity was independently positively associated with desphospho-uncarboxylated MGP (dp-ucMGP) [β coeff = 0.098, p=0.006]. 1SD of Lp-PLA2 activity was associated with 37% increased risk (p=0.001) of elevated dp-ucMGP (≥977 pmol/L, top quartile). In the Cox proportional hazard model adjusted for conventional risk factors, the patients in the highest quartile of dp-ucMGP or lowest quintile of total-uncarboxylated ucMGP (<2660 nmol/L) had higher risk of all-cause mortality [HRR 2.79 (95% CI 1.97-3.94) and HRR 1.69 (95% CI 1.18-2.42), respectively]. We observed no effect of high Lp-PLA2 activity (≥195 nmol/min/mL) on total mortality. CONCLUSIONS: We assume that Lp-PLA2 is involved in vascular calcification and that dp-ucMGP is a more appropriate biomarker of residual risk than Lp-PLA2 itself.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Proportional Hazards Models; Prospective Studies; Humans; Netherlands; proporcionální rizikové modely; kardiovaskulární nemoci; lidé středního věku; prospektivní studie; proteiny vázající vápník; Middle Aged; Nizozemsko; Cardiovascular Diseases; Calcium-Binding Proteins; Risk Factors; mužské pohlaví; rizikové faktory; biologické markery; ženské pohlaví; lidé; analýza přežití; Biomarkers; Aged; 1-alkyl-2-acetylglycerofosfocholinesterasa; senioři; Male; Extracellular Matrix Proteins; extracelulární matrix - proteiny; Survival Analysis; Female